(untitled) (Fiep Bulletin - online, 2014)
The present work is to report the implementation of the plan of bodily practices therapeutic physical education in CAPS AD “EspaçoAcolher” de Macapá/AP, as well as the inclusion of residents of Physical Education who are part of the Multiprofessional Residency Program in Community Health Area concentration of Mental Health . Thus, the overall goal is to share the experiences of the resident’s physical education in CAPS AD for deploying service physical education teacher. And as a specific objective to emphasize actions and practices body therapies performed in CAPS ad by residents in the everyday, and disseminate experiences that contribute to the formation and performance of physical education teachers in mental health service. The report covers the experience that occurred from May 10th October 2nd 2013 , which contains one hundred and three registers on field diary , which were divided into three steps : setting , planning and execution during service , this way were seven vignettes were separated from the diary . Thus , it is emphasized that physical education space in mental health through bodily practices , yoga , hiking , rhythmtherapy , gymnastics and games and sports, enhances the patient in recovery / rescue treatment culture , autonomy , behavior change , critical sense , living in groups, creativity and improvement in their physical well being, mental , spiritual and social , making it an important therapeutic tool for composing the therapeutic CAPS .